Integrasi Sastra Arab dan Islam serta Pengaruhnya Terhadap Sastrawan Muslim Modern - Qois Azizah Bin Has; Muhammad Zaky Sya’bani (Institut Agama Islam Negeri Metro, 2020)
In his work, some modern Muslim literature shows a relationship between Arabic literature and Islam. This is shown in some of the literary works of Muslim writers who made Islam a Worldview and thought in his writing. Abu Bakar Siradjuddin, for example, who persistently spread Islam in Europe through his Literary Works and received a good response was even followed by several other poets. In contrast to Siradjuddin, Ahmad Al Alawi, an Algerian poet, also spread Islam through his 1955 manuscripts and literary books. This shows that the existence of Arabic and Islamic literature is still sustainable. Although on the other hand, there are new cultures, but this does not change the pattern of Muslim Literature. This article uses a description analysis method to describe the study of the Integration of Arabic and Islamic literature as an object of art and life revealed from the soul with full faith in Islam. So the resulting Texts also hold on to the view of Islamic life. (Islamic Worldview)